Trajetoria de decisões administrativas na unidade camponesa e na empresa agropecuária capitalista:estudo de casos no Sul de Minas Gerais - Jesus, José Carlos dos Santos (1993)
This work was carried out with the objective of understanding the decision-making process in a Peasant Production Unit and in an Agricultural Enterprise, both in Southern Region of Minas Gerais State . The study was based on the Action Theory which enabled the establishment of an analitical framework intended to study the following articulations: means, conditions, and goals which had been ponderated by producers who were interviewed. In order to study the decisions themselves the interpretative analysis was used from the productor's view. His life story was used as a starting point for the decision process reconstitution. At the Pessant Production Unit all decisions were taken on the ground of ponderations on Iimiting factors such as: land, work, and funds associated to the objectives of profit increase at minimum risks and subsistence garantee. As a result, a survalval strategy arised characterized by the articulation between agriculture and commerce what meant a logical adjustment among goals, means, and conditions. At the Agricultural Enterprise, however, the articulation among farming, livestock raising and commerce enabled the differentiation between a family and a farm enterprise, which was also favored by the following factors: land availability and easy acess to either technical or rural credit what enabled the use of hired workmanship as well investments on the productive process. The different ways of articulating farming,- raising and commerce represented how means and conditions were adjusted to the different objectives stablished during the decision process. From late 1970's an increasing influence from the family members who were agronomist upon the interprise decision was noticed. Such an influence caused an increase in both the technological and the administrative level as well as a reformulation of actions goals and strategies what gave that production unit a noticeable enterprise aspect. Both survival! and capital accumulation stratagies were based on the articulation between agriculture and commerce which is a way for the farmer to face agricultural policies. The social differenciation process was determined by the following factors: land ownership; available starting patrimony(land and improvements) acess to institutional benefits(technical assistance and subsidized credit); adoption of technological innovations; family; farming,- livestock raising, and commerce.